2015
DOI: 10.1109/jlt.2015.2448795
|View full text |Cite
|
Sign up to set email alerts
|

Label-Free Detection of Tumor Angiogenesis Biomarker Angiopoietin 2 Using Bloch Surface Waves on One Dimensional Photonic Crystals

Abstract: We describe the design and fabrication of biochips based on 1-D photonic crystals supporting Bloch surface waves for label-free optical biosensing. The optical properties of Bloch surface waves are studied in relation to the geometry of the photonic crystals and on the properties of the dielectric materials used for the fabrication. The planar stacks of the biochips are composed of silica, tantala, and titania that were deposited using plasma-ion-assisted evaporation under high-vacuum conditions. The biochip s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 25 publications
1
27
0
1
Order By: Relevance
“…Very recently, Sinibaldi et al [23] pointed out a first preliminary distinction regarding this question, providing also an equation that relates the volume RI sensitivity to the surface sensitivity of the proposed biosensor.…”
Section: Fundamentals Of Optical Fiber Gratingsmentioning
confidence: 99%
“…Very recently, Sinibaldi et al [23] pointed out a first preliminary distinction regarding this question, providing also an equation that relates the volume RI sensitivity to the surface sensitivity of the proposed biosensor.…”
Section: Fundamentals Of Optical Fiber Gratingsmentioning
confidence: 99%
“…4 are analyzed according to procedures that are commonly reported in literature (Wang et al, 2009), one can evaluate the limit of detection in the label-free mode as LoD LF = 2 LF / S LF = (11.5 ± 0.5) ng/mL. The LoD LF can be expressed in terms of the minimum mass coverage detectable in the label free mode by making use of the following expression (Sinibaldi et al, 2015b):…”
Section: Label-free and Fluorescence Calibration Curves In D-pbsmentioning
confidence: 99%
“…For such a reason, fluorescence schemes exploiting evanescent waves, featuring strong field localization and intensity enhancement at the surface of interest, have been employed (Anopchenko et al, 2016;Cooper, 2002;Descrovi et al, 2013;Fan et al, 2008;Ligler and Taitt, 2008;Zhao et al, 2010). Among evanescent wave sensors, those based on Bloch surface waves (BSW) sustained by dielectric one dimensional photonic crystals (1DPC) (Yeh et al, 1977) have been demonstrated as an effective alternative to SPR for label-free optical biosensing (Konopsky et al, 2013;Rivolo et al, 2012;Rizzo et al, 2014;Shinn and Robertson, 2005;Sinibaldi et al, 2015aSinibaldi et al, , 2015b. The direct comparison of the performance of BSW with SPR biosensors showed that evanescent waves on all-dielectric structures can outperform their metallic analogue (Sinibaldi et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Here, we present the detection of both Ang2 spiked in buffer and endogenous Ang2 biomarker directly from human blood plasma, with the sensing platform operating in the fluorescence mode only. While several BSW based biosensors [19,22,[24][25][26][27] were reported for the detection of different analytes, their accuracy was never tested with real clinical samples. Blood plasma, together with serum, is one of the main sources of clinical analytes [28].…”
Section: Introductionmentioning
confidence: 99%